TRANSPORT SERVICE SYSTEM DESIGN USING MODIFIED APRIORI ALGORITHM - Otu, Godwin A.; Achimugu, Philip; Owolabi, Adeyemi; Raphael, Ugbe U.; Abdullahi, Monday J.; Shukurah, Oyebanji Modupeola; Blamah, Nachamada Vachaku; Usman, Sakinate L. (FUDMA JOURNAL OF SCIENCES, 2022)
This research is carried-out to evaluate the effectiveness of data mining in determining viability of routes, efficient scheduling and assigning of vehicles to commuters. The study was guided by the following objectives: modification of Apriori algorithm, implementation using C programming language, analyses and deductions from the results to determine if a given route is feasible. Data Mining (association rule) technique has been used to identify geographical locations where accidents have occurred and their characteristics, in road management to develop effective accident preventive measures, to determine estimated travel time and in market basket analysis applied in grocery stores. Data was collected from three transport companies for each route. The data was inputted into the program implemented using modified Apriori algorithm. The study findings revealed the volume of commuters per route and how vehicles can be assigned and scheduled. Using the above findings, effective transport service system is designed using routes viability
Keywords: Apriori, scheduling, assigning, viability.